A mixed methods approach to developing and evaluating oncology trainee education around minimization of adverse events and improved patient quality and safety. Issue 1 (December 2016) - Janssen, Anna; Shaw, Tim; Bradbury, Lauren; Moujaber, Tania; Nørrelykke, Anne; Zerillo, Jessica; LaCasce, Ann; Co, John; Robinson, Tracy; Starr, Alison; Harnett, Paul
Abstract Background Adverse events are a significant quality and safety issue in the hospital setting due to their direct impact on patients. Additionally, such events are often handled by junior doctors due to their direct involvement with patients. As such, it is important for health care organizations to prioritize education and training for junior doctors on identifying adverse events and handling them when they occur. The Cancer Cup Challenge is an educational program focuses on quality improvement and adverse event awareness targeting for junior oncology doctors across three international sites. Methods A mixed methodology was used to develop and evaluate the program. The Qstream spaced learning platform was used to disseminate information to participants, as it has been demonstrated to impact on both knowledge and behavior. Eight short case based scenarios with expert feedback were developed by a multidisciplinary advisory committee containing representatives from the international sites. At the conclusion of the course impact on participant knowledge was evaluated using analysis of the metrics collected by the Qstream platform. Additionally, an online survey and semi-structured interviews were used to evaluate engagement and perceived value by participants. Results A total of 35 junior doctors registered to undertake the Qstream program, with 31 (88.57 %) successfully completing it. Analysis of the Qstream metrics revealed 76.57 % of cases were answered correctly on first attempt. The post-program survey received 17 responses, with 76.47 % indicating cases for the course were interesting and 82.35 % feeling cases were relevant. Finally, 14 participants consented to participate in semi-structured interviews about the program, with feedback towards the course being generally very positive. Conclusions Our study demonstrates that an online game is well accepted by junior doctors as a method to increase their quality improvement awareness. Developing effective and sustainable training for doctors is important to ensure positive patient outcomes are maintained in the hospital setting. This is particularly important for junior doctors as they are working closely with patients and learning skills and behaviors, which will influence their practice throughout their careers.